Adaptation Issues Of Children With Cochlear Implants Within The Framework Of General Inclusive Education In Armenia - Harutyunyan, Inessa
This article provides comprehensive information about hearing impairments, specialized methods for hearing restoration, such as cochlear implantation, as well as the goals, timing, stages, and age-specific features of auditory and speech rehabilitation after cochlear implantation. It also highlights the factors that contribute to and hinder the social adaptation of children with cochlear implants (CI). The article discusses challenges in preschool and school education for children with CI, such as the lack of special technical tools to enhance the quality of education, insufficient awareness among educators and teachers regarding communication with children with CI, and the psychological aspects of their interactions with peers.
Keywords: Education